Fast transformation in e-business environments: third party fulfilment adaptation to online retailer demands - Alexander, Paul (IADIS press, 2010)
The paper extends previous UK surveys of third party e-fulfilment (3PEF) providers servicing a new segment of online retailers that has generated new sales opportunities for provision of their particular logistics needs. An index of capability transformation previously developed is applied to 6 Australian cases to determine the mechanism for this capability transformation; that is, the process and incentives for establishing new capabilities, transforming older capabilities, and also discontinuing specific capabilities. It proposes a model in which each sales transaction serves as a decision node at which a capability is established, expanded, transformed or discontinued. In this model, over a relatively short period there will be a large number of sales transactions which will drive evolution of the 3PEF at a potentially fast rate, with sales revenue as an incentive to modify capabilities transaction by transaction.